PERAN GURU PAI DALAM MEMBENTUK KARAKTER RELIGIUS SISWA DI SD NEGERI 03 UNGARAN - Sutrisno, Eri; Ayep Rosidi; Matori (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2026)
The role of Islamic Religious Education (PAI) teachers within the scope of primary education is vital in shaping students' religious character. Religious character is typically identified through several aspects, such as education, knowledge, competence, and awareness in implementing religious culture. Various studies on religious character education have been conducted; research using a qualitative approach aims to form students' religious character in the digital era. The method used in this research is qualitative and descriptive with a field approach. Interviews and direct practice were also applied in this study. The research subjects targeted 30 fifth-grade students at SDN Bandarjo 03 Ungaran, located at Jl. Gatot Subroto No.123a, Bandarjo Village, West Ungaran District, Semarang Regency, Central Java Province, 50511. This research took place for one month (30 days), starting from December 15, 2025, to January 15, 2026. Data collection was carried out through documentative literature study, observation, and interviews. The literature study was conducted by distributing questionnaires and holding photography sessions. Observation was carried out by collecting responses from the questionnaire results. Interviews were conducted by asking a series of questions to identify student character. As supporting data, direct practice in the aspect of discipline—such as cultivating timely prayers and wearing modest clothing (covering the aurat)—was also considered in this study. The results showed that the role of PAI teachers in forming students' religious character at SD Negeri 03 Ungaran through literature, interviews, observation, and direct practice methods enabled students to apply Islamic religious values such as discipline, diligence, honesty, responsibility, and others, which serve as a solid foundation for students in facing modernization. These results indicate that the method is highly effective and feasible for practical application in the field.